2010
DOI: 10.1074/jbc.m109.074005
|View full text |Cite
|
Sign up to set email alerts
|

A Conformational Switch in the Scaffolding Protein NHERF1 Controls Autoinhibition and Complex Formation

Abstract: The mammalian Na؉ /H ؉ exchange regulatory factor 1 (NHERF1) is a multidomain scaffolding protein essential for regulating the intracellular trafficking and macromolecular assembly of transmembrane ion channels and receptors. NHERF1 consists of tandem PDZ-1, PDZ-2 domains that interact with the cytoplasmic domains of membrane proteins and a C-terminal (CT) domain that binds the membrane-cytoskeleton linker protein ezrin. NHERF1 is held in an autoinhibited state through intramolecular interactions between PDZ2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 69 publications
5
79
0
Order By: Relevance
“…3B), the second PDZ domain (PDZ2) is considerably more stable in denaturing conditions and also able to bind a CFTR peptide with increased (~10-fold higher) affinity. Similar to PSD-95 PDZ3, the extension does not seem to have a large impact on the fold of the canonical domain; superimposition of the structures of an extended and truncated form show that there is little deviation in the backbone conformation (Bhattacharya et al, 2010). It certainly seems that the NHERF1 PDZ2 extension and PSD-95 PDZ3 extension have many conserved structural and functional features.…”
Section: Roles Of Pdz Extensionsmentioning
confidence: 95%
“…3B), the second PDZ domain (PDZ2) is considerably more stable in denaturing conditions and also able to bind a CFTR peptide with increased (~10-fold higher) affinity. Similar to PSD-95 PDZ3, the extension does not seem to have a large impact on the fold of the canonical domain; superimposition of the structures of an extended and truncated form show that there is little deviation in the backbone conformation (Bhattacharya et al, 2010). It certainly seems that the NHERF1 PDZ2 extension and PSD-95 PDZ3 extension have many conserved structural and functional features.…”
Section: Roles Of Pdz Extensionsmentioning
confidence: 95%
“…15 Their results showed that residues 0 to -5 (See The additional C-terminal extension is not unique for PDZ3. 25,26 In MAGI PDZ1 for example, an extended C-terminal loop makes direct interactions with Arg -4 , Arg -5 and Thr -6 of the peptide ligand and mutation in this C-terminal loop decreases the binding affinity drastically. 27 Thus, from previous work 11,12,14,24,27 together with the present data we conclude that some PDZ domains contain certain structural elements at their C-terminus, which have a direct effect on binding affinity.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Autoinhibition is increasingly seen in proteins involved in a diverse set of biological phenomena. [15][16][17][20][21][22][23] Mechanisms that are known to relieve autoinhibition include posttranslational modification, proteolysis, and addition of proteins or small ligands. The mechanisms and especially the thermodynamics and kinetics of the activation process in autoregulated proteins are generally poorly understood.…”
Section: Introductionmentioning
confidence: 99%